THE IMPACT OF PLANNING, PROGRAM TRANSPARENCY, AND MASLAHAH-BASED UTILIZATION ON THE SUCCESS OF THE VILLAGE FUND PROGRAM (A CASE STUDY OF TAMANG ISLAND) - Alisa, Intan; Rahma, Tri Inda Fadhila; Atika, Atika (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2026)
Abstract This study aims to analyze the effect of planning, program transparency, and maslahah-based utilization on the success of the Village Fund Program in Pulau Tamang. The research employed a quantitative approach with an associative research design. The population consisted of 578 village residents, and a sample of 85 respondents was determined using the Slovin formula with a 10% margin of error. Data were collected through questionnaires and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and the coefficient of determination (R Square). The results indicate that partially, planning, program transparency, and maslahah-based utilization have a significant effect on the success of the Village Fund Program, with significance values below 0.05. Simultaneously, the three variables also have a significant effect, with an F-value of 26.108 and a significance of 0.000. The R Square value of 0.492 shows that 49.2% of the variation in program success can be explained by these variables. Thus, the success of the Village Fund Program is influenced by systematic planning, accountable transparency, and maslahah-oriented fund utilization. Keywords: Planning, Transparency, Maslahah, Village Fund, Program Success